Clinical association with non-hodgkin lymphoma - Abdullah, Wan Zaidah (Pusat Pengajian Sains Peubatan, Universiti Sains Malaysia, 2004)
Introduction: The association of anti phospholipid antibodies (APA) with Non..Hodgkin Lymphoma~) has been reported and complete remission was associated with disappearance of APA. APA are autoantibodies which include anticardiolipin antibody (ACA), anti-beta2-glycoprotein-I (~2 GPI) antibodies and lupus anticoagulant (LA). Objective: The purpose of this study was to determine the prevalence of APA and its clinical association among NHL patients in our institution. Meth~dology: A study was conducted ~n Hospital· Unive~sity Science Malaysia . . .. . (HUSM) between June 2003 and July 2004. Fifty-three selected NHL patients · were tested for ACA and anti-~2 GPI at presentation using ELISA technique. They were followed-u'p over a median period of 6 months to detect the occurrence of thromboembolism (TE} and bone marrow recovery following chemotherapy using full blood counts. Results: APA was found in 23 out of 53 NHL patients, with ACA 35.8o/o and anti( 32 GPI antibodies 18.9o/o. The incidence of elevated APA was increased after 40. years old (91.3°/o). However, positivity for APA was not associated with gender, survival, histology or stage of lymphoma. There were three patients who developed TE and all of them were ACA positive. Positive APA was found to correlate with thrombocytopenia at presentation (p= 0.032) and associated with poor platelet recovery following chemotherapy (p=0.001 ). Conclusion: APA was common among NHL patients especially after 40 years old. Although no statis~ical association was found between APA positive NHL and thrombosis, there was a tendency forTE to occur in APA positive NHL.